Cross-cultural research of adolescents’ ethnic identity features - Shandro, I. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The article dwells on the question of ethnic self-consciousness formation among the representatives of various ethnic groups through the study of their ethnic identity. Ethnic identity forming is observed through the study oа the attitude of the adolescents being tested towards ethnically-differentiating and ethnically-integrating indicators of the ethnos, as well as the study of the adolescents’ vision concerning the image of the representatives of their own and the other ethnos.